Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Liny Jaya Informatika Makassar - Aminah Aminah; Andi Irfan; Claudya Armelia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of work discipline on employee performance at PT Liny Jaya informatics Makassar. The method used in this research is quantitative with the number of respondents 40 employees who are used as samples with sampling techniques, namely saturated samples. The data used in this study are primary data obtained directly from data sources using a questionnaire. The data analysis method uses reliability test, validation test, simple linear regression test, coefficient of determination, hypothesis testing (T test). The test results of work discipline variables have a positive and significant effect on employee performance variables.